"Well-Designed Relations": Cold War Design Exchanges between Brussels and Moscow in the Early 1970s. (4th May 2017) - Serulus, Katarina
Abstract: The importance of design in Cold War diplomacy is widely acknowledged in historical accounts. High-profile international exhibitions and industrial shows were prominent battlegrounds where the United States and the Soviet Union locked horns on living standards and consumption regimes. Instead of examining these sites of confrontation, this article examines the lesser-known design exchanges between Brussels and Moscow in the early 1970s. Not only were the commercial prospects of the Cold War détente of paramount importance to this interaction beyond the Iron Curtain, but also the far-flung network of prominent design personalities beyond governmental structures. It was especially through the transnational network of the International Council of Societies of Industrial Design (ICSID) that the East and West design scenes could meet.